Historic and linguistic code of turkic laws «tore bitik» - Eshmetova, B B; Shegebayeva U А; Kusherbayeva A.Zh. А Zh (Journal of Oriental Studies, 2016)
The Kazakh language is a direct descendant of the ancient Kypchak language, and that is why, no doubt in the value of medieval Kypchak written monuments based on the Armenian letter in the studies of scholars on the history of the language. Therefore, we consider a gem of writing as «Tore bіtіgі» which has come to us from our ancestors. «Tore bіtіgі» – is a collection of legal norms of Kypchaks of that time, which addresses important areas of life such as social, economic, political, administrative, family, commercial, criminal relationships. There are rules relating to the punishment for the crime and the legal terms that are not used in the modern Kazakh language. For example: toreshі, zhargyshy (judge), zhaksylar alkasy (jurors) tore (laws, regulations, generally regarded individuals and legal entities), etc. Also the monument describes the procedure of taking the oath in the judging.